y = (-3)x + 7
2007-01-15 10:19:59
·
answer #1
·
answered by WingIV 2
·
1⤊
0⤋
The equation for a line is y= mx+b
y = (-3)x + b
where m= gradient or slope of the line and b is the y-intercept
so your equation = y= -3x +7
2007-01-15 18:23:02
·
answer #2
·
answered by K J 1
·
0⤊
0⤋
the equation of the line is y = mx + b where m is the slope and b is the y intercept. therefore your line is y = -3x + 7
2007-01-15 18:20:58
·
answer #3
·
answered by 1ofSelby's 6
·
1⤊
0⤋
First: you need to know the slope-intercept form...
y = mx + b
Sec: replace - 3 with "m" and replace 7 with "b"
y = - 3x + 7
2007-01-15 18:21:08
·
answer #4
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
To start you need to know the slope-intercept form:
y=mx+b
therfore you have y=-3x+7
2007-01-15 18:26:20
·
answer #5
·
answered by guitarist 1
·
0⤊
0⤋
The eqn is y = mx + b
y = -3x + 7
2007-01-15 18:24:48
·
answer #6
·
answered by sg 2
·
0⤊
0⤋
3x+7
2007-01-15 18:19:56
·
answer #7
·
answered by cheeseburger42593 2
·
0⤊
1⤋
y=mx+b
y = -3x + 7
2007-01-15 18:21:10
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
y= -3x+7
2007-01-15 18:21:47
·
answer #9
·
answered by mcluver_8 2
·
0⤊
0⤋
y=-3x+7
2007-01-15 18:30:13
·
answer #10
·
answered by A 150 Days Of Flood 4
·
0⤊
0⤋